Application of pulse width modulation technique in air humidity control system - Pakdeekaew, Aphisik; Treeamnuk, Krawee; Treeamnuk, Tawarat; Wongbubpa, Nuttapong (Agriculture and Natural Resources, 2023)
Importance of the work: A method was presented for controlling the humidity ratio of the mixture of emitted air from a dryer with fresh air so that it can be applied to reduce energy consumption in the future. Objectives: To develop a control system with a pulse width modulation (PWM) technique for air humidity ratio control in a laboratory-scale paddy drying system. Materials & Methods: An on-off air control valve with PWM was controlled using two methods: 1) theoretical calculation; and 2) the second of Ziegler-Nichol’s methods consisting of Proportional-integral (PI)-, Proportional-integral-derivative (PID)- and PID-no overshoot controls, respectively. Results: A closed-loop control system based on Ziegler-Nichols’ second method achieved the fastest steady-state response, especially with a PID controller. The performance of Ziegler-Nichols’ second method was closer to the reference values at a steady state than the theoretical calculation method. Main finding: All the proposed methods produced low error in steady-state responses with averages less than 3.691%. All methods were suitable for various applications, with sufficient potential for application in controlling the humidity ratio of air in the drying process of agricultural products.